Mathematical concepts in calculating Zakat Maal based on the Al-Qur'an perspective - Nur Azizah; Mohammad Tohir (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2024)
This research aims to reveal mathematical concepts in calculating Zakat Maal as explained in the Al-Qur'an. This research is qualitative descriptive research with a literature review type. The sources used as references in writing are the Al-Qur'an, books, and national and international journals relevant to the research study. The data collection methods used are observation and documentation, while the data analysis technique used in this research is content analysis. The results of the research show that mathematical concepts are found in Zakat Maal, namely in gold and silver Zakat, trade Zakat and professional Zakat (the concept of relations and functions, the idea of sets), agricultural Zakat and Rikaz ZAKAT (the concept of fractional rational numbers). The recommendation for further research is to expand the literature in the hope that later, we can obtain better results and discussions and develop an exploration of other mathematical concepts in calculating Zakat Maal.